Youth suicide risk screening in an outpatient child abuse clinic. Issue 1 (10th June 2021) - Ngai, Margaret; Delaney, Kathleen; Limandri, Barbara; Dreves, Kristin; Tipton, Mary V.; Horowitz, Lisa M.
Abstract: Problem: Child abuse is an important independent risk factor for suicide. The purpose of the project was to evaluate the implementation of a universal suicide risk screening and assessment tool in an outpatient child abuse evaluation clinic. Methods: Participants consisted of all patients between the ages of 10 and 18 years who received services at the study site within a 3‐month period ( n  = 162). The study site implemented a tool created for the sole purpose of detecting suicide risk, the Ask Suicide‐Screening Questions (ASQ) tool. Data was retrospectively collected using electronic health records; rates of compliance with screening and screen positive rates were calculated. Findings: Suicide risk screening with the ASQ was conducted on 90.7% (147) of the patients. Forty‐three (29.2%) patients screened positive for suicide risk. This is a significant increase in detection rates compared to baseline preimplementation data. Of the 67 preteens, 10–12 years of age, that were screened, 14.9% (10/67) screened positive for suicide risk, making up 23% of the positive screens. Conclusions: Implementing a universal suicide risk screening tool was a successful strategy for detecting suicide risk. A quarter of the youth who screened positive on the ASQ were preteens, highlighting the importance of screening the 10‐ to 12‐year olds for suicide risk.